STUDY ON VARIOUS HABITAT COMPONENTS OF PUNJAB URIAL IN ITS DISTRIBUTION RANGE - S. Suleman1; W. A. Khan; K. M. Anjum; W. Shehzad; S. G. M. D. Hashmi; Attaullah; K. Iqbal; R. Raja (Journal of Animal and Plant Sciences, 2021)
The present study is the first of its kind being reported from Pakistan for Punjab Urial (Ovis Vignei Punjabiensis) which was aimed towards assessing various components of its habitat (vegetation, food preference, land cover, and water) throughout the whole of its distribution range viz. Salt Range (Chakwal, Jehlum, Khushab, Kohat and Mianwali Districts) and Kala Chitta Range (Attock District). For assessment of vegetation in the whole study area (64 study sites), all dominant plant species of potential habitat were studied by quadrate method while the food of Punjab Urial was identified on predetermined line transects. Concurrently, a total of 180 water samples were obtained for various water quality attributes. A total of 74 families including 284 species were identified with Poaceae (21 %) as a majorly contributing family, followed by Asteracea (6 %), Solanaceae (3 %), and the remaining being within the range of 0.7 to 1 %. Within this vegetation, herbs, grasses, trees and shrubs were 56 %, 16 %, 16 % and 12 %, respectively. Overall, 51 % of food of Punjab Urial comprised of herbs while the rest of it was grasses, trees and shrubs being 19, 16 and 14 %, respectively. All the studied water quality attributes had a statistical difference (P ≤ 0.05) within districts of study with Kohat having least quality.
Keywords: Punjab Urial; Ovis vignei punjabiensis; Habitat components